2022
DOI: 10.3389/fphys.2022.792052
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Aerobic Window of Horses in Response to Training by Means of a Modified Lactate Minimum Speed Test: Flatten the Curve

Abstract: There is a great need for objective external training load prescription and performance capacity evaluation in equestrian disciplines. Therefore, reliable standardised exercise tests (SETs) are needed. Classic SETs require maximum intensities with associated risks to deduce training loads from pre-described cut-off values. The lactate minimum speed (LMS) test could be a valuable alternative. Our aim was to compare new performance parameters of a modified LMS-test with those of an incremental SET, to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 69 publications
(134 reference statements)
0
27
1
Order By: Relevance
“…Previous studies have shown that young Friesian horses transfer to anaerobic metabolism, measured by LA > 4 mmol/L, on relatively low intensity work [48,49]. Using a single cut-off point for LA related to HR or velocity, such as HR LA4 or V LA4 , is not the best predictor for the anaerobic threshold [64,65]; horses often cannot maintain LA constant for a longer period of time on that specific velocity or HR. A fixed cut-off value is often an overestimation of the lactate threshold [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that young Friesian horses transfer to anaerobic metabolism, measured by LA > 4 mmol/L, on relatively low intensity work [48,49]. Using a single cut-off point for LA related to HR or velocity, such as HR LA4 or V LA4 , is not the best predictor for the anaerobic threshold [64,65]; horses often cannot maintain LA constant for a longer period of time on that specific velocity or HR. A fixed cut-off value is often an overestimation of the lactate threshold [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Using a single cut-off point for LA related to HR or velocity, such as HR LA4 or V LA4 , is not the best predictor for the anaerobic threshold [64,65]; horses often cannot maintain LA constant for a longer period of time on that specific velocity or HR. A fixed cut-off value is often an overestimation of the lactate threshold [65][66][67]. Several tests are described to assess the intensity of exercise that leads to a steady state in lactate production, removal and metabolism and the threshold where anaerobic glycolysis participation starts to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were withdrawn from the left jugular vein and immediately evaluated on‐site by direct measurement of blood lactate concentrations using a portable hand‐held device (Lactate Pro2, Axon Lab AG), previously validated 17 and tested in horses 18 …”
Section: Methodsmentioning
confidence: 99%
“…Despite advancements in technology and research, much animal training, such as horse training, is still conducted based on empirical methods. These methods are often based on widespread protocols that are not tailored to each animal’s capabilities ( Cunha et al, 2009 ; Ferasin and Marcora, 2009 ; Manzo et al, 2009 ; Alves et al, 2012 ; Rodrigues et al, 2017 ; Impellizzeri et al, 2019 ; Restan et al, 2019 ; De Maré et al, 2022 ). Lactate threshold (LT) is a key marker for running performance and lactate-guided conditioning program has become a cornerstone of endurance training ( Dyson, 2002 ; Poole and Erickson, 2008 ; Singer et al, 2008 ; Peyré-Tartaruga and Coertjens, 2018 ; Impellizzeri et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%